Real-time precise measurements of ocean surface waves using GNSS variometric approach - Yang Liu; Menghao Li; Yanxiong Liu; Yanfeng Wang; Shumin Jiang; Yabin Wang; Li Tian; Fangli Qiao (International Journal of Applied Earth Observations and Geoinformation, 2022)
The global navigation satellite system (GNSS) wave buoys currently in use can measure ocean surface waves but have major drawbacks regarding their real-time high-precision application due to the communication burden and high differential correction service costs; these issues have heavily limited the large-scale deployment of GNSS wave buoys globally. In this work, we propose a global real-time low-cost centimeter-level precise wave measurement method using onboard GNSS variometric velocities and segment wave parameter retrievals. The proposed novel method can achieve buoy velocities with millimeter-level accuracies using freely available broadcast ephemerides and clocks. In addition, surface wave parameters can be accurately retrieved online in real time at a GNSS variometric sampling rate of 2.5 Hz or above. The variometric approach retrieved significant wave height and mean wave period differences of 3.4 cm and 0.16 s, respectively, compared to those measured by the classical Datawell wave buoy, reaching the performance of precise point positioning results that can be obtained using precise ephemerides and clocks. In addition, the proposed method markedly outperformed the Doppler approach, especially in terms of the buoy velocity accuracy and displacement determination. The proposed GNSS variometric approach has promising application potential in real-time precise surface wave measurement applications at remarkably low costs, thus strongly supporting global ocean observations.